IDENTIFICATION OF POWER AND ENERGY PARAMETERS OF DIGGING CUTTING-PROJECTILE WORKING BODY (Academic journal Industrial Machine Building Civil Engineering, 2017)
The paper presents the results of a study ofpower and energy parameters of the process of digging cutting-projectile working body. Keywords:energy parameters, cutting- projectile working body, coat cutting.